Analyzing Spiritual Potential in Tafsir And Hadith, Ecoteological Integration - Alim Bakhri; Azzahra Shabina Humairah Arsyad; Marhani Marhani (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to analyze the spiritual potential from the perspective of Qur'anic exegesis and Hadith and to integrate it into the framework of Islamic ecotheology in order to develop a paradigm of ecological awareness based on spirituality. The study employed a qualitative approach using library research. Primary data sources consisted of the Qur'an, authentic Hadiths, and classical as well as contemporary tafsir literature, while secondary data were obtained from books and scientific journals related to ecotheology, Islamic spirituality, and environmental ethics. Data collection was conducted through documentation studies, while data analysis employed content analysis with an interpretative approach through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the human spiritual structure, which includes the qalb (heart), nafs (self/soul), and ruh (spirit), functions as the center of moral consciousness that influences human ecological behavior. Qur'anic exegesis and Hadith also contain ecotheological values ​​through the concepts of khalifah fil ardh (vicegerency on earth), mizan (balance), amanah (trust), and the prohibition of facade fil ardh (corruption on earth), all of which emphasize human responsibility in maintaining environmental balance. The integration of spirituality and ecotheology produces the paradigm of Islamic spiritual ecology, namely the conceptual relationship between tazkiyah al-nafs (self-purification), tawhidic consciousness, ecological ethics, and Islamic ecotheology. This study concludes that environmental crises are caused not only by social and material factors but are also closely related to the spiritual crisis of humanity. Therefore, strengthening spiritual awareness becomes an essential part of developing sustainable environmental ethics from an Islamic perspective.